Sharing Knowledge of Occupational Issue in Indonesia and Thailand - Pramitasari, Ratih; Sifai, Izzatul Alifah; Aprianti, Aprianti; Treesak, Chalobon (Research Collaboration Community (RCC), 2025)
Occupational Safety and Health (OSH) remain critical issues in Southeast Asia, particularly in Indonesia and Thailand, where industrial growth has led to an increase in workplace accidents and occupational diseases. This study focuses on an international community service collaboration between Thammasat University in Thailand and Indonesian institutions. The program aims to enhance students' understanding of OSH challenges, share knowledge on workplace accident prevention, and introduce ergonomics-based health promotion media. The activities included presentations, discussions, and evaluations to measure knowledge improvement. Results indicated that students significantly increased their understanding of OSH principles, as evidenced by high scores on post-activity quizzes. Additionally, the introduction of ergonomics-based health promotion media highlighted its potential as a preventive tool in addressing workplace hazards. This program underscores the importance of cross-border collaborations in advancing workplace safety and offers insights for scaling similar initiatives across ASEAN countries.